A genome-wide association study with tissue transcriptomics identifies genetic drivers for classic bladder exstrophy - Mingardo, Enrico; Beaman, Glenda; Grote, Philip; Nordenskjöld, Agneta; Newman, William; Woolf, Adrian S.; Eckstein, Markus; Hilger, Alina C.; Dworschak, Gabriel C.; Rösch, Wolfgang; Ebert, Anne-Karolin; Stein, Raimund; et al. (Communications biology, 2022)
Classic bladder exstrophy represents the most severe end of all human congenital anomalies of the kidney and urinary tract and is associated with bladder cancer susceptibility. Previous genetic studies identified one locus to be involved in classic bladder exstrophy, but were limited to a restrict number of cohort. Here we show the largest classic bladder exstrophy genome-wide association analysis to date where we identify eight genome-wide significant loci, seven of which are novel. In these regions reside ten coding and four non-coding genes. Among the coding genes is EFNA1, strongly expressed in mouse embryonic genital tubercle, urethra, and primitive bladder. Re-sequence of EFNA1 in the investigated classic bladder exstrophy cohort of our study displays an enrichment of rare protein altering variants. We show that all coding genes are expressed and/or significantly regulated in both mouse and human embryonic developmental bladder stages. Furthermore, nine of the coding genes residing in the regions of genome-wide significance are differentially expressed in bladder cancers. Our data suggest genetic drivers for classic bladder exstrophy, as well as a possible role for these drivers to relevant bladder cancer susceptibility.
Gesehen am 18.07.2023